In Vitro Biological Activity of Beauveria bassiana, Beauveria peruviensis, and Metarhizium sp. against Hypothenemus hampei (Coleoptera: Curculionidae) - Beimer Chuquibala-Checan; Magdiel Torres-de la Cruz; Santos Leiva; Elgar Hernandez-Diaz; Karol Rubio; Malluri Goñas; Marielita Arce-Inga; Manuel Oliva-Cruz (International Journal of Agronomy)
Coffee (Coffea arabica) is the main commodity in Peru and is the economic support for thousands of small farmers. However, coffee production is affected by the coffee berry borer (Hypothenemus hampei). Currently, H. hampei is the most important pest in whole coffee-growing regions in Peru. This study aimed to evaluate in vitro biological activity of Beauveria bassiana, Beauveria peruviensis, and Metarhizium sp. against Hypothenemus hampei in two trials at different times. Conidia production, Conidia viability, and pathogenicity against H. hampei were evaluated at three concentrations (1 × 105, 1 × 107, and 1 × 109 conidia/mL−1). In addition, lethal times (LT50 and LT90) and lethal concentrations (LC50 and LC90) were calculated. There were significant differences in conidia production (P < 0.001) and conidia viability (P < 0.041). The highest conidia production and conidia viability were reached by B. bassiana and B. peruviensis, respectively. Likewise, there were differences in the pathogenicity of the strains in the two tests carried out (test 1: P < 0.0009 and test 2: P < 0.0001). The highest mortality occurred in the treatments of B. bassiana 1 × 109 conidia/mL−1, B. bassiana 1 × 107 conidia/mL−1, and B. peruviensis 1 × 109 conidia/mL−1. The treatments with lower LT50 and LT90 were B. bassiana 1 × 109 conidia/mL−1 and B. peruviensis 1 × 109 conidia/mL−1, and the strains with the lowest LC50 and LC90 were B. peruviensis and B. bassiana. The in vitro characteristics shown by B. bassiana and B. peruviensis conditions suggest they should be evaluated in the field to determine the capability of these strains to reduce populations of H. hampei.